Identification of gene mutations associated with type 1 diabetes by next-generation sequencing in affected Palestinian families - Bawatneh, Abrar; Darwish, Alaa; Eideh, Hasan; Darwish, Hisham M. (Frontiers in Genetics, 2024)
Introduction: Diabetes Mellitus is a group of metabolic disorders characterized by hyperglycemia secondary to insulin resistance or deficiency. It is considered a major health problem worldwide. T1DM is a result of a combination of genetics, epigenetics, and environmental factors. Several genes have been associated with T1DM, including HLA, INS, CTLA4, and PTPN22. However, none of these findings have been based on linkage analysis because it is rare to find families with several diabetic individuals. Two Palestinian families with several afflicted members with variations in the mode of inheritance were identified and selected for this study. This study aimed to identify the putative causative gene(s) responsible for T1DM development in these families to improve our understanding of the molecular genetics of the disease. Methods: One afflicted member from each family was selected for Whole-Exome Sequencing. Data were mapped to the reference of the human genome, and the resulting VCF file data were filtered. The variants with the highest phenotype correlation score were checked by Sanger sequencing for all family members. The confirmed variants were analyzed in silico by bioinformatics tools. Results: In one family, the IGF1R p.V579F variant, which follows autosomal dominant inheritance, was confirmed and segregated in the family. In another family, the NEUROD1 p.P197H variant, which follows autosomal recessive inheritance, was positively confirmed and segregated. Conclusion:IGF1R p.V579F and NEUROD1 p.P197H variants were associated with T1DM development in the two inflicted families. Further analysis and functional assays will be performed, including the generation of mutant model cell systems, to unravel their specific molecular mechanism in the disease development.